Nephroprotective Effect of Naringenin and Bromelain Against Cisplatin-Induced Renal Toxicity in Rats - Pansare, Kajal; Ahire, Yogesh; Bairagi, Vinod (Trends in Sciences, 2024)
Cisplatin is a widely used chemotherapeutic agent known for its dose-limiting nephrotoxicity, which significantly hampers its clinical utility. The present study evaluates the nephroprotective potential of Naringenin and Bromelain, natural compounds with established antioxidant and anti-inflammatory properties, administered alone and in combination against cisplatin-induced nephropathy in rats. Adult Wistar rats were divided into eight groups: normal control, cisplatin control, standard treatment with N-acetylcysteine (NAC) and various treatment groups receiving Naringenin and Bromelain at low and high doses, both alone and in combination. Nephropathy was induced using a single intraperitoneal dose of cisplatin (7 mg/kg) at day 0. Treatments were administered orally for 14 consecutive days. Parameters like body and kidney weight, kidney hypertrophy index, serum biochemical markers (urea, creatinine, uric acid), oxidative stress markers (LPO, NO), pro-inflammatory cytokines (TNF-α, IL-6) and histopathological changes in renal tissue were evaluated. Cisplatin administration resulted in significant renal impairment, as indicated by weight alterations, elevated serum biochemical markers, increased oxidative and inflammatory markers and marked renal histological damage. Treatment with NAC and both natural compounds ameliorated these pathological changes. Notably, the combination of high-dose Naringenin and Bromelain demonstrated the most substantial nephroprotective effects, restoring biochemical and inflammatory parameters near normal levels and preserving renal histoarchitecture. These findings suggest a synergistic effect likely mediated through combined antioxidant and anti-inflammatory mechanisms. The study concludes that Naringenin and Bromelain, particularly when administered together at higher doses, exert significant protective effects against cisplatin-induced nephropathy. These natural agents may serve as promising adjunctive therapies to mitigate cisplatin-associated renal damage. HIGHLIGHTS Naringenin and Bromelain, alone and in combination, were evaluated for their nephroprotective effects in a cisplatin-induced rat model of nephropathy. Combination therapy significantly attenuated cisplatin-induced elevations in serum urea, uric acid, creatinine, and oxidative stress markers. Co-administration of high-dose Naringenin and Bromelain significantly reduced pro-inflammatory cytokines (TNF-α, IL-6) and preserved renal histological architecture. The study demonstrates a synergistic antioxidant and anti-inflammatory effect of Naringenin and Bromelain, suggesting their therapeutic potential against cisplatin nephrotoxicity. GRAPHICAL ABSTRACT